(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Background: Smoking is associated with dysregulation of the antioxidant system and addiction. Aim: This study sought to ascertain the effect of Nigella Sativa (NS) oil on the antioxidant system, nicotine/tobacco addiction as well as the expressions of α4β2 nicotinic (nAChR) and dopamine type-2 (DRD2) receptors in selected brain regions of the rat. Methods: Thirty male Sprague-Dawley rats were divided into 6 groups comprising of vehicle-treated control, NS oil only, Smoke only, Smoke + NS oil, Nicotine only and Nicotine + NS oil. Animals were passively exposed to cigarette smoke or nicotine vapour for 12 weeks, however, NS oil treatment commenced from 9th-12th week of the experimental duration. Results: Nicotine vapour and cigarette smoke-induced increase in cotinine level were significantly ameliorated by NS treatment. Cigarette smoke or nicotine vapour exposure significantly (p<0.05) decreased the level of antioxidant enzymes while increasing malondialdehyde level in the brain homogenates of the rats. Administration of NS oil significantly (p<0.05) reversed the reduced antioxidant level. Cigarette-smoke also significantly increased α4-nAChR expression in the frontal cortex and olfactory bulb compared to control. Nicotine vapour significantly increased DRD2 expression only in the olfactory cortex. NS oil administration reduced both the cigarette-smoke-induced increase in α4-nAChR and nicotine vapour-induced increase in DRD2 gene expression only in the olfactory cortex. Conclusion: Findings from this study suggest that NS oil improves brain antioxidant status while ameliorating nicotine vapour and cigarette smoke addiction through down-regulation of α4-nAChR and DRD2 gene expressions in discrete brain regions in Sprague-Dawley rats.